Feng Shui and Theory of Place: Navigating Chinese Traditional Cosmology in Modern Ecology - Refan Aditya (Published by Confucius Institute UNS, 2025)
This article is a theoretical review on Feng Shui in ecological discourse. Even though Feng Shui has always been about environmentalism, nature, and the harmonisation of humans with their environment, discussions of Feng Shui in the context of modern ecological science are relatively rare, or at least less popular. This is because Feng Shui, in modern and urban society, is treated more as pragmatic measures than ecological knowledge. This research aims to provide theoretical insights that engage Feng Shui in the discourse of ecology and modernity by grounding it in the theory of place put forward by Brian G. Cambel. The theory of place postulated that place holds a particular meaning for ethical commitment for human-nature living. There are three approaches to place: phenomenology, bioregionalism, and cultural geography. This research argues that these three approaches provide a paradigmatic grounding for the critical relevance of Feng Shui in modern ecology discourse, regardless of its non-scientific and superstitious reputation.